Two new clam shrimp species (Crustacea: Branchiopoda: Spinicaudata) from Kerala, India - Babu, K. K Subhash; Nandan, S. Bijoy (Zootaxa, 2010)
Two new clam shrimp species belonging to the genera Eulimnadia Packard, 1874 and Leptestheria Sars 1898 from Kerala, India are described. Spinicaudatan clam shrimp are among the least studied groups in India, with only 30 species reported. Eulimnadia azisi sp. nov. was collected from rain fed, temporary, rocky depressions at Vettilapara, in Western Ghats, Kerala. No males were observed and the population may be hermaphroditic. Leptestheria dumonti sp. nov. was collected from the paddy fields at Parapukara, Kerala. Altogether two species of Leptestheria and nine species of Eulimnadia have been reported from India, and this is the first report of the genus Leptestheria from Kerala.